2018
DOI: 10.1016/j.ophtha.2017.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Prediction of Glaucoma Progression Under Different Target Intraocular Pressure Levels Using Filtered Forecasting Methods

Abstract: To our knowledge, this is the first clinical decision-making tool that generates personalized forecasts of the trajectory of OAG progression at different target IOP levels. This approach can help clinicians determine appropriate, personalized target IOPs for patients with OAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 24 publications
(21 reference statements)
0
34
0
1
Order By: Relevance
“…Although intraocular pressure (IOP)-lowering has been shown to be therapeutically effective in delaying glaucoma progression, some demonstrated that disease progression is still inevitable,54–56 suggesting that we have not arrived at optimised treatment regimens for the various forms of glaucoma. Kazemian et al 57 developed a clinical forecasting tool that uses tonometric and VF data to project disease trajectories at different target IOPs. Further refinement of this tool that integrates other ophthalmic and non-ophthalmic data would be useful to establish target IOPs and the best strategies to achieve them on a case-by-case basis.…”
Section: Applications In Ophthalmologymentioning
confidence: 99%
“…Although intraocular pressure (IOP)-lowering has been shown to be therapeutically effective in delaying glaucoma progression, some demonstrated that disease progression is still inevitable,54–56 suggesting that we have not arrived at optimised treatment regimens for the various forms of glaucoma. Kazemian et al 57 developed a clinical forecasting tool that uses tonometric and VF data to project disease trajectories at different target IOPs. Further refinement of this tool that integrates other ophthalmic and non-ophthalmic data would be useful to establish target IOPs and the best strategies to achieve them on a case-by-case basis.…”
Section: Applications In Ophthalmologymentioning
confidence: 99%
“…1. self-reported white British ancestry ("in_white_British_ancestry_subset" column) 2. used to compute principal components ("used_in_pca_calculation" column) 3. not marked as outliers for heterozygosity and missing rates ("het_missing_outliers" column)…”
Section: Genome-wide Association Analysis In Uk Biobankmentioning
confidence: 99%
“…Intraocular pressure (IOP) is a modifiable risk factor and predictive measure for glaucoma [1][2][3][4] (S1 Fig). Genome-wide association studies (GWAS) have commonly used this endophenotype that exhibits high genetic correlation (rg = 0.71) to glaucoma, as an approach to prioritize genetic variants likely to contribute to disease risk [5].…”
Section: Introductionmentioning
confidence: 99%
“…This would be useful information before a resident embarks on a rotation as the primary surgeon in a high volume general ophthalmology rotation. This pooling of data has been successfully done with assessment of glaucoma progression 14,15 as well as many unrelated disciplines with the commonality of multiple inputs, measurable outcomes, and many data points. Finally, providing the residents with statistically based feedback from learning studies can assist in changing behavior.…”
Section: Discussionmentioning
confidence: 99%